Global Transcriptome Analysis and Identification of Differentially Expressed Genes in Strawberry after Preharvest Application of Benzothiadiazole and Chitosan - Landi, Lucia; De Miccolis Angelini, Rita M.; Pollastro, Stefania; Feliziani, Erica; Faretra, Franco; Romanazzi, Gianfranco (Frontiers in Plant Science, 2017)
The use of resistance inducers is a novel strategy to elicit defense responses in strawberry fruit to protect against preharvest and postharvest decay. However, the mechanisms behind the specific resistance inducers are not completely understood. Here, global transcriptional changes in strawberry fruit were investigated using RNA-Seq technology. Preharvest, benzothiadiazole (BTH) and chitosan were applied to the plant canopy, and the fruit were harvested at 6, 12, and 24 h post-treatment. Overall, 5,062 and 5,210 differentially expressed genes (fold change ≥ 2) were identified in these fruits under the BTH and chitosan treatments, respectively, as compared to the control expression. About 80% of these genes were differentially expressed by both elicitors. Comprehensive functional enrichment analysis highlighted different gene modulation over time for transcripts associated with photosynthesis and heat-shock proteins, according to elicitor. Up-regulation of genes associated with reprogramming of protein metabolism was observed in fruit treated with both elicitors, which led to increased storage proteins. Several genes associated with the plant immune system, hormone metabolism, systemic acquired resistance, and biotic and abiotic stresses were differentially expressed in treated versus untreated plants. The RNA-Seq output was confirmed using RT-qPCR for 12 selected genes. This study demonstrates that these two elicitors affect cell networks associated with plant defenses in different ways, and suggests a role for chloroplasts as the primary target in this modulation of the plant defense responses, which actively communicate these signals through changes in redox status. The genes identified in this study represent markers to better elucidate plant/pathogen/resistance-inducer interactions, and to plan novel sustainable disease management strategies.